Storytelling in northern Zambia : theory, method, practice and other necessary fictions - Cancel, Robert (World oral literature series ;, 2013)
"Storytelling plays an important part in the vibrant cultural life of Zambia in in man other communities across Africa. This innovative book provides a collection and analysis of oral narrative traditions as practiced by five Bemba-speaking ethnic groups in Zambia. The integration of newly digitalized audio and video recordings into the texst enables the reader to encounter the storytellers themselves and hear their narratives."--Publisher's description